Beliefs and actions in the trust game: Creating instrumental variables to estimate the causal effect - Miguel A. Costa-Gomes; Steffen Huck; Georg Weizsäcker (Games and Economic Behavior, 2014)
In many economic contexts, an elusive variable of interest is the agent's belief about relevant events, e.g. about other agents' behavior. A growing number of surveys and experiments asks participants to state beliefs explicitly but little is known about the causal relation between beliefs and actions. This paper discusses the possibility of creating exogenous instrumental variables for belief statements, by informing the agent about exogenous manipulations of the relevant events. We conduct trust game experiments where the amount sent back by the second player (trustee) is exogenously varied. The procedure allows detecting causal links from beliefs to actions under plausible assumptions. The IV-estimated effect is significant, confirming the causal role of beliefs.
Keywords: C72; C81; C91; D84; 330; social capital; trust game; instrumental variables; belief elicitation